Influence of nitrogen addition on soil respiration and soil properties in urban forests in Hefei city in China - Yueqin Chen; Honghua Ruan (PLoS ONE, 2025)
With the continuous development of urbanization, nitrogen deposition has affected the regeneration capacity of urban forest soil. This study focused on Quercus acutissima Carruth forest in a southern city Hefei in China. The effects of different nitrogen addition rates on both the soil respiration rate and the soil properties of urban forests were studied. In addition, the effects of seasonal changes on soil respiration were also analyzed. The experimental results showed that low nitrogen addition rate (5 g·m-2·yr-1) increased soil respiration rate by about 11% in summer, but decreased it by about 6% in winter, with a range of 5% to 20%. High nitrogen addition (15 g·m-2·yr-1) significantly increased soil temperature by about 12% in summer (p < 0.05), and significantly decreased soil temperature by about 13% in winter (p < 0.05), indicating the seasonal regulation effect of nitrogen addition on soil temperature. As a result, the soil respiration rate was 3.26 ± 0.45 μmol m-2·s-1 in summer and 0.51 ± 0.07 μmol m-2·s-1 in winter. The results indicated that the high nitrogen addition had a significant effect on soil respiration rate, which increased in summer and decreased in winter. Soil moisture content and temperature had significant effects on soil respiration rate, especially in the suburban test site. Nitrogen addition significantly increased soil total nitrogen and nitrate nitrogen contents (p < 0.05), but had no significant effect on soil pH value. Structural equation modeling analysis showed that nitrogen addition promoted soil microbial activity, releases heat, and thus increases soil temperature. Meanwhile, this method affected soil respiration rate, soil moisture, soil total nitrogen, and nitrate nitrogen content, directly or indirectly regulating soil heterotrophic respiration and autotrophic respiration. In conclusion, this study revealed the significant effects of nitrogen addition on urban forest soil respiration and its components, which provided data support and theoretical reference for understanding the dynamic changes of urban ecosystem carbon cycle, and was of great significance for guiding future urban greening and ecological protection work.